Are EU budget deficits stationary? (2010)
In this paper, we test for the stationarity of European Union budget deficits over the period 1971-2006, using a panel of thirteen member countries. Our testing strategy addresses two key concerns with regard to unit root panel data testing, namely (1) the presence of cross-sectional dependence among the countries in the panel and (2) the identification of potential structural breaks that might have occurred at different points in time. To address these concerns, we employ an AR-based bootstrap approach that allows us to test the null hypothesis of joint stationarity with endogenously determined structural breaks. In contrast to the existing literature, we find that the EU countries considered are characterised by fiscal stationarity over the full sample period irrespective of us allowing for structural breaks. This conclusion also holds when analysing sub-periods based on before and after the Maastricht treaty. © Springer-Verlag 2009.